Characterization of the endophytic fungal communities associated to Coleostephus myconis: looking for potential repellent/attractant compounds towards Philaenus spumarius - Cameirão, Cristina (2019)
Philaenus spumarius is a xylem feeding insect identified so far as the only vector involved in the first European outbreak of the phytobacterium Xylella fastidiosa, affecting and devastating olive groves in Italy. One approach to reduce X. fastidiosa transmission could rely in the vector control through the use of baits to attract and/or repel de insect. Fungal endophytes inhabiting plants provide a source of candidate repellent/attractant compounds. In this work, the endophytic fungi community associated to the weed Coleostephus myconis, was studied in order to identified potential fungi that can be used as attractants or repellents of P. spumarius. Coleostephus myconis is common in olive groves and preferentially used by P. spumarius for the nymph development. Fungi were isolated from the stems, leaves and inflorescences from plants with three levels of P. spumarius infestation (i.e. no infestation, moderate and high infestation). The fungal isolates obtained were identified by sequencing the ITS region of rDNA and the partial tef1. Overall, was obtained 138 taxa belonging to 37 different genera. The endophytic community composition differs between infested and non-infested plants, solely at stems level, where the P. spumarius foam nests are present. The fungal genera, Cytospora, Diaporthe and Penicillium, which are well-known with producers of volatiles compounds repellent activity against insect, were found only on non-infested plants. Botrytis was restricted to infested plants. The behavioral responses and preferences of P. spumarius for C. myconis plants colonized by these endophytes should be investigated in the future.